Exploring Finger Digit Ratios (2D:4D) in Surgeons, Professional Rugby Players, and Political Journalists to Form a Directional Hypothesis: Could Finger Length Predict Attention and Focus? - Serpell, Benjamin G.; Cook, Christian J. (Frontiers in Behavioral Neuroscience, 2022)
In this short report we explore the predictive nature of finger digit ratio (i.e., second/index finger length divided by fourth/ring finger length; 2D:4D) and achievement. This research, with niche and specialized populations, was intended to support and grow on knowledge obtained from other large population 2D:4D studies and help form a directional hypothesis for future work exploring finger digit ratio and 'success'. Twenty-nine professional rugby players aged 25.1 ± 4.2 years, height 185.2 ± 6.3 cm and weight 101.9 ± 11.8 kg; n = 16 orthopedic surgeons aged 55.3 ± 9.3 years with height 183.8 ± 10.2 cm and weight 90.8 ± 14.0 kg; and n = 18 political journalists with age, height and weight of 38.8 ± 7.3 years, 182.8 ± 7.8 cm and 84.4 ± 11.4 kg respectively were recruited. Three experiments were conducted where we 1) explored relationships for 2D:4D with testosterone and cortisol responsiveness to low stress exercise, 2) explored relationships for 2D:4D with pupil constriction and pupil constriction latency (pupillometry measures related to testosterone and cortisol responsiveness and to attentiveness), and 3) compared 2D:4D between rugby players, surgeons, and journalists. Our results revealed 2D:4D was not predictive of testosterone and cortisol responsiveness to low-level exercise stress. However, relationships exist for 2D:4D and pupillometry measures (p<0.05). Journalists right minus left 2D:4D difference was significantly different to rugby players' and surgeons (p<0.05). We argue 2D:4D is likely predictive of testosterone sensitivity and associated ability to focus attention; a skill important to high achievement in various contexts